2021
DOI: 10.20944/preprints202110.0140.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of Biodegradation Performance of Marine Sponge Symbiont Bacteria Consortium Against Anthracene and Pyrene

Abstract: Every petroleum processing industry produces sewage sludge containing several types of poly-cyclic aromatic hydrocarbon (PAHs) components. The degradation of PAH components by physical, biological and chemical methods is not efficient. The use of marine sponge symbiont bacteria is considered an alternative method in the degradation and reduction of PAHs com-pared to the previous method. This study aims to explore the potential and performance of a consortium of sponge symbiont bacteria in degrading anthracene … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…An interesting study of Marzuki et al (2021) focused on the role of sponges in the biomonitoring of heavy metals such as chromium, cadmium, polycyclic aromatic hydrocarbons (PAHs), and naphthalene. The authors conducted experiments, which allowed them to evaluate the biodegradation power of these pollutants by the symbiotic bacteria in the sponges.…”
Section: Heavy Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting study of Marzuki et al (2021) focused on the role of sponges in the biomonitoring of heavy metals such as chromium, cadmium, polycyclic aromatic hydrocarbons (PAHs), and naphthalene. The authors conducted experiments, which allowed them to evaluate the biodegradation power of these pollutants by the symbiotic bacteria in the sponges.…”
Section: Heavy Metalsmentioning
confidence: 99%
“…Gupta and Kiran (2017) isolated a lipopeptide from the marine sponge F. cavernosa (MMD32 strain), which was able to degrade PAHs, forming a micellar system that solubilizes the hydrophobic substrate and reduces surface tension. Phenanthrene and pyrene at a concentration of 100 mg/L were degraded in 7 days, and in 5 days the pyrene was reduced to a concentration of 8.425 mg. Marzuki et al (2021) explored the ability of marine sponges Niphate sp., Hyrtios erectus, and Clathria to resist the presence of PAHs. These authors demonstrated that B. pumilus, P. stutzeri, and Acinetobacter calcoaceticus associated to all sponges examined degraded anthracene and pyrene.…”
Section: Microplasticsmentioning
confidence: 99%